FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN KOLOSTRUM PADA IBU MENYUSUI DI PUSKESMAS BANDAR SIANTAR KEC. GUNUNG MALELA KAB. SIMALUNGUNTAHUN 2021 - Peny Ariani; Eka Sri Wahyuni; Fadilla Rasanty; Destin Stefani Waruwu; Suriani Suriani (JURNAL ILMIAH DHDT - KEBIDANAN, 2021)
Introduction: Breast milk contains growth factors and antibody substances. Growth factors in breast milk play a role in helping the maturation process of organs and hormones, while antibody substances serve to help the immune system maturation process. If breast milk is not given exclusively, the process of maturation of the immune system will be disrupted and cause the baby to develop infections easily. A mother's success in breastfeeding is influenced by many factors, namely: predisposing factors, possible factors and booster factors (Green 1980 in Notoatmojo, 2016). Purpose: This researcher aims to find out how factors related to the administration of colostrum in nursing mothers in the Puskesmas Bandar Siantar District Gunung Malela Simalungun district in 202I year 202I. Method: research in analytical surveys with cross sectional approach. The population of this study is nursing mothers in the Puskesmas Bandar Siantar District Mount Malela Simalungun district in 202I amounted to 41 people (Accidental sampling). Result: From the results of the study of 41 respondents, after a statistic test using chi-square test obtained there is a relationship of predisposition factors (age with chi-squere 0.002 < 0.05, education with chi-squere 0.001 < 0.05, knowledge with chi-squere 0.000 < 0.05, source of information with chi-squere 0.03 < 0.05.), booster factor (husband support with chi-squere 0.004 < 0.05 and health worker support with chi-squere 0.002 < 0.05). by giving colostrum to nursing mothers in the Puskesmas Bandar Siantar District Mount Malela Simalungun District in 202I. Conclusion: it is recommended to health officials to increase public knowledge about breast milk by expanding the target of health promotion regarding breast milk not only nursing mothers but also in other family members. in nursing mothers, in The Health Center Bandar Siantar District Mount Malela Simalungun district in 202I.